(untitled) (Journal of Management and Educational Sciences, 2025)
This study aims to examine the impact of communication skills on conflict resolution styles among married individuals. Marital relationships are dynamic and complex structures in which individuals unite socially, emotionally, and economically. Conflicts are inevitable in this process, and communication skills play a pivotal role in managing them. The literature emphasizes that effective communication includes empathy, clear self-expression, and active listening, which contribute significantly to marital satisfaction. In this context, determining the effect of communication competence on conflict resolution styles is critical for enhancing family harmony and strengthening marital bonds. The study employs a relational survey model and was conducted with 426 married individuals residing in Konya, Turkey, selected through convenience sampling. Data were collected using a personal information form, the Communication Skills Scale (developed by Korkut-Owen & Demirbaş Çelik, 2017), and the Conflict Resolution Styles in Romantic Relationships Scale (developed by Özen, 2016). Data analysis was performed using SPSS 25, employing Pearson correlation and multiple linear regression techniques. Findings indicate a positive but low-level significant relationship between communication skills and conflict resolution styles, with a moderate correlation observed specifically between constructive resolution strategies and communication skills. Regression analysis reveals that communication skills have a limited predictive power on conflict resolution styles, with only the “willingness to communicate” sub-dimension approaching significance. These results suggest that conflict resolution cannot be explained solely by communication competence; other psychosocial variables such as personality traits, attachment styles, and marital duration also play a role. In conclusion, the findings highlight that developing effective communication skills supports the adoption of constructive behaviors in conflict resolution processes. The study underscores the importance of communication-focused interventions in marital counseling and family therapy and recommends further research in diverse sociocultural contexts to enhance generalizability.